Green Practice Leading to Green Hotel at Clay Craft Restaurant, Renaissance Bali Uluwatu Resort & Spa - Saputra, Kadek Vandy Darma; Sari, I Gusti Agung Mas Krisna Komala; Triyuni, Ni Nyoman (Journal of Business on Hospitality and Tourism, 2022)
Implementing green hotel is very important to protect environment. One of each department that implements green practice in this hotel is the beverage & food department, However, in practice, Clay Craft Restaurant has not been maximized in the application of green practice regarding green practice. The research work was conducted to analyses the implementation of green practice at Clay Craft Restaurant and green practice lead to green hotel at Renaissance Bali Uluwatu Resort & Spa. The variables used are green practice and green hotel. The total key persons are five. Data collection method used are interview, documentation, questionnaires. Data analysis technique used are descriptive qualitative and descriptive statistics. The implementation of green practice has a percentage value of 79,17 percent. Consist of, Green Food (100,00 percent), Green Action (87,50 percent), andGreen Donation (50,00 percent). Green Practice lead to the Green Hotel show an percentage value of 79,22 percent.Clay Craft Restaurant should improve the implementation of Green Practice to all indicators, especially the green donationand green action.